How can we better align private security with the public interest? Towards a civilizing model of regulation. Issue 2 (22nd December 2015) - Loader, Ian; White, Adam
Abstract: How can we better align private security with the public interest? This question has met with two answers in the literature on private security regulation, one seeking to cleanse the market of deviant sellers, the other to communalize the market through the empowerment of buyers. Both models of regulation are premised upon a limited neoclassical economic conception of how market transactions map onto the public interest. This article makes the case for a new model of regulation, one that seeks to civilize the market. Drawing upon the insights of economic sociology, our model regards the market for security as a moral economy in which commodity and non‐commodity values jostle and collide. On this basis, we propose a regulatory architecture where buyers and sellers are cast not only as economic actors but also as moral actors, revealing new avenues through which to encompass private security within the democratic promise of security.